(untitled) (Konturen, 2012)
The present work explores the separation barriers built by the Israeli government and military as products and producers of asymmetries of power between Israelis and Palestinians; and, at the same time, as products and producers of discourses that are characterized by the naturalization of evil. In such discourses, evil is singularized as a unique cultural property of the national adversary; violence and aggression on the part of the adversary are perceived as a sign of a primitive morality, detached from political and historical circumstances; and violence of each party is justified as a defensive war on the “evil” other. A return to Melanie Klein allows to trace these dynamics, and to raise fundamental questions on the role of the cultural analyst.